In another world, my sister stole my name. 2 - Kotoko (Light novel and manga author) (Yen Press, 2025)
Transmigrated to another world and forced to live as "Karen," Ichika is frustrated about her sister, the saint who stole her identity. But when she saves her fiancée Noah from a curse, it's revealed that she is a saint as well! Now, armed with knowledge of the magic she wields, Ichika takes on a job to purify a river together with Noah. As the two grow closer even through bickering, Ichika discovers a whole new power residing within her...